God, Mind, Evolution, and Quantum Reality Based on Process Metaphysics - Germine, Mark (Tattva Journal of Philosophy, 2016)
The genesis of actuality from potentiality, with the apparent role of the observer, is an important and unsolved problem which essentially defines science‟s view of reality in a variety of contexts. Observation then becomes lawful and not emergent. Panentheism is needed to provide a mechanism for order outside of blind efficient causality, in a Universal final causality. Classical physics is over a hundred years out of date, yet scientific models remain mechanistic and deterministic. Deism, a remnant of classical cosmology, is examined and rejected by scientists and philosophers, and certain pre-scientific notions of religion are scorned, putting the matter to rest. Quantum physics, in its basic form, is necessary if there is to be any philosophical or scientific notion of free will and self-determination, as potentiality. Quantum metaphysics is also needed because classical physics is fundamentally limited to localized external relations, lacking the internality and non-locality of relatedness. God, or the equivalent, is necessary to complete the equation. Physicists now tell us that reality is fundamentally mental and is created by observation. Observation is here taken to mean experience, with experience going all the way down to the lowest order of a Universal mentality.